The poliomielíticas forms of the Peruvian wart - Trelles, J. O. (1956)
In the course of Carrion's disease, bartonella committed when the central nervous system, only very rarely direct aggression of the spinal cord was observed. Myelitis bartonelósica boxes only have been the subject of clinical observation, because generally evolve towards improvement and healing; and even when the presence of Bartonella in the CSF has been reported in cases of meningoencephalitis verrucosa in the core boxes could not do this, it not to conduct an anatomical study for full confirmation of lesion location in bartonerlosis spinal cord.